2009
DOI: 10.1007/s12272-009-1902-x
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic, antipyretic, anti-inflammatory and toxic effects of andrographolide derivatives in experimental animals

Abstract: Andrographolide (1) and 14-deoxy-11,12-didehydroandrographolide (2) are active constituents of Andrographis paniculata (Burm. f.), family Acanthaceae. A. paniculata extracts are reported to have antiviral, antipyretic, immunostimulant and anticancer activities. In this study, 1 and its 14-acetyl- (4) and 3,19-isopropylidenyl- (3) derivatives, as well as 2 and its 3,19-dipalmitoyl-derivative (5), were intraperitoneally tested for their analgesic, antipyretic, anti-inflammatory and acute toxicity effects in anim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(67 citation statements)
references
References 24 publications
2
63
0
2
Order By: Relevance
“…14-Deoxy-11,12-didehydro-andrographolide. The 1 H-NMR and 13 C-NMR data are identical with Suebsasana et al (7).…”
Section: In Vitro Antivenin Activity Of C Contravenenum Formulationssupporting
confidence: 83%
“…14-Deoxy-11,12-didehydro-andrographolide. The 1 H-NMR and 13 C-NMR data are identical with Suebsasana et al (7).…”
Section: In Vitro Antivenin Activity Of C Contravenenum Formulationssupporting
confidence: 83%
“…Similar studies carried out by Kamaraj et al (2010b) Control-nil mortality a Mean value of five replicates±SD been observed earlier by Bagavan et al (2009) that the potential of acaricidal and flukicidal activity of leaf hexane extract of Annona squamosa, methanol extracts of Gloriosa superba, and Phyllanthus emblica against H. bispinosa (LC 50 = 145.39, 225.57, and 256.08 ppm); methanol extracts of Centella asiatica and G. superba against P. cervi (LC 50 =77.61and 60.16 ppm). Andrographolide (1) and 14-deoxy-11, 12-didehydroandrographolide (2) were isolated from A. paniculata and reported to have antiviral, antipyretic, immunostimulant, and anticancer activities (Suebsasana et al 2009). Alkaloids isolated from A. squamosa have shown larvicidal growth-regulating and chemosterilant activities against Anopheles stephensi at concentrations of 50-200 ppm; the larvae, pupae, and adults produced about a 52-92% decrease in the laboratory experiment (Saxena et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Andrographolide is also a starting point for the semisynthesis of other labdane diterpenes [46][47][48]. …”
Section: Minor Labdane Diterpenesmentioning
confidence: 99%